School Absenteeism of Adolescent Girls during Menstruation in Khagrachari, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Adolescent girls in underdeveloped nations often struggle with menstrual hygiene, especially when they are in school. Poor menstrual hygiene in impoverished nations has not received enough attention up until now. This study aimed to find the state of adolescent girls who miss school when menstruating and the association between school absenteeism and various factors related to menstruation. Materials and methods: A descriptive type of cross-sectional study was conducted during the period January to December 2019 with 300 adolescent school girls in a rural hilly area in Bangladesh. A self-administered questionnaire was used to collect data and analysis of results was done according to standard statistical analysis by using SPSS version 22. Results: Among 300 students, only 82 (27.3%) respondents remained absent during menstruation, among those 27.3% respondents, more than two-thirds of the students (74.4%) were absent from school/college due to physical discomfort or lower abdominal pain. One seventy-four (58%) girls used other than sanitary pads (cloth or rags) during menstruation. Out of 174 non-pad users, 118(67.8%) were of (the 16-18) years group.Among the respondents who used sanitary pads, 36.5% were Hindu, 95.2% were unmarried and 20.6% were from the upper class.The chisquare test revealed menstrual hygiene was strongly associated with ethnicity, religion and SES but school absenteeism was not influenced by menstrual hygiene (c2= 0.410, p0.522 ). Conclusion: School authorities implementation of school health programs for adolescents should emphasise menstrual hygiene, which is especially related to the use of sanitary pads, not unhygienic rags or clothes.Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 77-82